Prevalence of abuse and related factors in a Colombian medical school (Colombia Medica, 2024)
Introduction: Different forms of abusive practices are very common in medical schools and have serious implications on vocational and professional formation. The aim of this study is to determine the prevalence of perception of abuse in a university in Colombia and to identify associated factors.Methods: A cross-sectional study was conducted from September to December 2008 in a private medical school. A proportional cycle-based stratified sampling technique and randomized sampling per semester was done. Socio demographic, academic, and abuse-related variables were obtained.Results: One hundred twenty-eight students participated in the study. The prevalence of perception of abuse was 40.6%. The most common type of abuse was psychological (98%) and unjustified critique (10.9%), ridiculing (10.7%), shouting (10%), and discredit (9.5%) were the most frequent manifestations. Professors in preclinical courses were reported as the most prevalent abusers (25.9%), followed by clinical professors (19.8%). The frequency of abusive manifestations was rare (15.8% and 11.5%) in preclinical and clinical years, respectively. The abusive manifestations were most frequent in pathology and pediatrics in the preclinical and clinical years,  espectively. Nineteen percent of the victims of abuse reported such to somebody. The main consequences were desire to withdraw from the career (63.2%) and change of career (36.8%). Increased perception of abuse (OR: 4.74 95% IC: 1.9-11.4 p=0.001) was associated during the clinical years.Conclusions: Although abusive practices are more frequent during clinical years, they do not constitute a systematic behavior among medical students from a private university in Colombia in comparison with other  tudies.